Naxos Disease and Related Cardio-Cutaneous Syndromes - Alexandros Protonotarios, MD; Angeliki Asimaki, Ph.D; Cristina Basso, MD; Zafeirenia Xylouri, MD; Emanuele Monda, MD; Ioannis Protonotarios, MD; Giulia Crisci, MD; Dominic JR. Abrahms, MMBS, MD, MBA; Aris Anastasakis, MD; Loizos Antoniades, MD; Athanasios Bakalakos, MD; Andreina Carbone, MD; et al. (JACC: Advances)
Naxos disease is a rare autosomal recessive condition combining arrhythmogenic right ventricular cardiomyopathy, woolly hair, and palmoplantar keratoderma. The first identified causative variant was in the gene encoding the desmosomal protein plakoglobin. Naxos disease exhibits fibro-fatty myocardial replacement with immunohistological abnormalities in cardiac protein and signaling pathways, highlighting the role of inflammation and potential anti-inflammatory treatments. Childhood cutaneous signs precede cardiac features, which are diagnosed by familial and genetic evaluation, electrocardiography and cardiac imaging. Disease progression necessitates holistic care with risk management and lifestyle adjustments, often needing treatment for arrhythmia and heart failure. Similar phenotypes have been linked to desmoplakin and rarely desmocollin2 gene variants, highlighting the importance of familial and genetic evaluation. This document summarizes current knowledge on Naxos disease and related cardiocutaneous syndromes and initiates an international endeavor to collect and study all global cases, aiming to improve understanding, treatment, and patient care through shared data and research.